Clinic-epidemiological approach to diabetes mellitus 1 in children under 5 years. - Hussimy Marchena Morera; Alina Esther González Hermida; Jorge Luis Irizar Hernández; Yanet Fragoso Cordero; Idalmis Reyes Rodríguez (Medisur)
Diabetes mellitus 1 is of the most prevalent chronic endocrinophaty during childhood. Its appearance in earlier stages of life has increased. Mistakes are often made while dealing with children under five. The diagnoses and treatment of this disease prevent or delay the emergence of complications that can reduce the life quality of these children. The education related to this disease includes different treatment stages. As part of this educations and aimed to facilitate the early diagnosis and appropriate treatment, a review in this field was carried out.